Analisis Kompetensi Mahasiswa Calon Guru PAUD Universitas Musamus dalam Menyusun Instrumen Penilaian Pembelajaran PAUD - Yulia Olga Siba Sabon; Dite Umbara Alfansuri; Hajra Yansa; Minuk Riyana; Cristiana Normalita de Lima (Journal Education Innovation (JEI), 2025)
Early childhood education (ECD) assessment helps measure how well learners experience development in their learning. By implementing assessments correctly and accurately in accordance with assessment principles, the results can reliably reflect learners’ abilities and progress. The effective execution of assessment in ECD teaching is closely tied to teachers’ competence in conducting evaluations. As prospective ECD teachers, students in the Early Childhood Teacher Education (PGPAUD) program are required to possess strong competencies in designing and administering assessments. Therefore, this study was carried out to examine the competence of PGPAUD students in developing ECD learning assessment instruments. This descriptive study employed a qualitative data analysis process by comparing students’ portfolios against predetermined criteria. The results revealed that, out of nine students, five demonstrated strong ability in selecting assessment techniques and constructing instruments accurately according to the rubrics; three exhibited moderate competence, being able to determine suitable assessment techniques but requiring improvement in instrument development; and one showed insufficient competence in both selecting assessment techniques and developing assessment instruments.